EVALUATION OF TRITICALE: GENOTYPE BY ENVIRONMENT INTERACTION AND GGE BIPLOT ANALYSIS - H. Güngör; M. F. Çakir; Z. Dumlupinar (Journal of Animal and Plant Sciences, 2022)
Stability and the preferred response of genotypes over various environments are essential for plant breeders. Six registered cultivars (Truva, Alperbey, Collegial, Karma 2000, Melez 2001 and Tatlıcak 97) and two advanced lines (TR-Trp16 and TR-Avk16) were studied across six environments (E) during two growing seasons in 2016-2017 and 2017-2018 at three locations (Kırklareli, Tekirdağ and Edirne) in Turkey. Genotype (G), genotype × year (G × Y), genotype × location (G × L) and genotype × year × location (G × Y × L) interactions were found significant for all investigated traits. Grain yield of the genotypes ranged from 5539 to 6800 kg ha-1 and cultivar Collegial had the highest grain yield (6800 kg ha-1), while cultivar Melez 2001 had the lowest (5539 kg ha-1). In terms of years, grain yield was higher in 2017 (6466 kg ha-1) and lower in 2018 (6016 kg ha-1). Among the test environments, Edirne was the highest for grain yield (7872 kg ha-1) followed by Kırklareli (5638 kg ha-1) while Tekirdağ was the lowest (5214 kg ha-1). Tekirdağ 2018 was found as the most favourable environment in terms of grain yield. Results revealed that Collegial was the most superior genotype across environments and cultivar Alperbey was the most stable genotype. This study indicates that cultivar improvement efforts should be put on to develop triticale genotypes for the specific environments rather than a broad adaptation.
Keywords: Environment; GGE biplot; Grain yield; Stability; Triticale